Fashion Virtual Influencers: Antecedents Influencing Females’ Behavioral Intentions in Jordan - Almasri , Yazeed (Dirasat: Human and Social Sciences, 2023)
Objectives: Social media influencers and celebrities have traditionally been utilized by marketers. However, with the advancements in artificial intelligence, virtual influencers are gaining popularity on social media platforms. As a result, companies are compelled to incorporate this emerging trend into their social media campaigns. However, there is limited research available regarding the effectiveness criteria of virtual influencers to guide marketers in their selection decisions. Therefore, this study aims to investigate the attributes of virtual influencers that impact consumer behavioral intentions, specifically within the fashion domain. Methods:. To measure the antecedents to influencing behavioral intentions, 224 online surveys were distributed to female Instagram users selected through convenience sampling method. The empirical design of the study involoved several Instagram posts created as if by a virtual influencer promoting a fictional fashion brand. These posts measured the constructs related to the research questions, drawing from validated digital human and influencer marketing literature. The collected data was analyzed using the Partial Least Squares method. Results: The study findings revealed that content informativeness, bonding, expertise, human like attributes, and consumer innovativeness all had varying degrees of influence on behavioral intentions, with content informativeness being the most influential factor. Conclusions: The study contributes to the limited literature on virtual influencers and provides novel practical implications to marketers. It also suggests the need for further in-depth studies to identify effective attributes of virtual influencers.